Pembangunan Fondasi Keagamaan Islam Pada Anak Usia Dini Di TK Al-Khazainy Kadutomo Jiput Pandeglang - Iwan Ridwan; Jakaria Jakaria; Wardatul Ilmiah; Ima Maisaroh; Siti Muhibah; Ratu Amalia Hayani (UIN Sultan Maulana Hasanudin Banten, 2021)
Children are individuals who are experiencing development. Early childhood is an individual who is at the golden age stage where at this time the child is experiencing a high sense of curiosity about something as learning. The formation of superior human character is an all-time project in Islam. Therefore, in this paper, the author wants to find the right steps to build a religious foundation in children whose ending will develop into characters that reflect behavior based on religious values.The results of this study indicate that (1) the religious values ​​instilled in children are the values ​​of faith, morals and worship. (2) a) The methods used are modeling, habituation, parables, storytelling and dialogue. b) The results obtained are that the child is able and accustomed to praying without coercion, becomes accustomed to learning the Koran, loves Allah's creation and does good deeds. c) Other family members also have a share. d) The process is carried out anywhere and anytime. (3) Parents act as father and mother as well as friends. (4) The family environment and social environment have an influence on the process of cultivating religious values. (5) a) The supporting factors are the family environment and places of worship in the house. b) The inhibiting factor is the child's social environment and the limited time the parents have. Solutions to overcome inhibiting factors are to supervise children, reduce or limit children's play hours, and give advice to children.